Evolution of stepping stone detection and emerging applications - Omar, Mohd Nizam; Amphawan, Angela; Din, Roshidi (2012)
Stepping Stone Detection (SSD) is conventionally intended for the detection of series of host computers used by attackers to hide their track in a network or host environment.This paper discusses the evolution of SSD and potential applications in other emerging fields. Novel, unique SSD models will be presented for spam, backdoor and proxy detections and expressed mathematically. These preliminary models have promising solutions for addressing current problems in these areas and may be expanded on in the future.